Sustainable Agriculture: Impact on Public Health and Sustainable Development - Maksym Huzenko; Stanislav Kononenko (Health Economics and Management Review)
Sustainable agriculture involves the use of organic farming technologies, which excludes the use of growth stimulants, hormones and chemical additives in animal feeding as well as fertilisers with pesticides and other hazardous chemicals. Sustainable land management practices are aimed at preserving soils, water resources and biodiversity. They mitigate the effects of climate change by reducing greenhouse gas emissions and preserving natural environments. Organic agriculture produces environmentally friendly food that contains fewer harmful chemicals, potentially reducing the incidence of diet-related disorders such as cardiovascular diseases, diabetes and cancer. This study conducts a comprehensive bibliometric analysis (via VOSviewer 1.6.16, Bibliometrix / Biblioshiny App) to explore the sustainable agriculture impact on public health and sustainable development of nations. Applying the Scopus database, 427 relevant papers were reviewed to identify trends, influential works, and key research themes. The analysis reveals that sustainable agricultural practices, which aim to reduce environmental impact, conserve resources and enhance productivity, have gained increasing attention since the mid-1990s. Noteworthy, contributions include fundamental works, influential studies and various UN and WHO publications. The research highlights keywords such as agriculture, public health, nutrition, and food security. Leading countries in this research domain include the USA, China, Canada, India, and the UK, demonstrating extensive international collaboration. The findings underscore the critical role of sustainable agriculture in addressing global challenges, promoting environmental stewardship, and supporting socio-economic progress, which aligns with the UN Sustainable Development Goals. The study provides valuable insights into the development of sustainable practices and policies essential for future research and implementation.